Cardiac Transplantation in Friedreich Ataxia - Yoon, Grace (2012)
In this paper, we describe a 14-year-old boy with a confirmed diagnosis of Friedreich ataxia who underwent cardiac transplantation for left ventricular failure secondary to dilated cardiomyopathy with restrictive physiology. His neurological status prior to transplantation reflected early signs of neurologic disease, with evidence of dysarthria, weakness, mild gait impairment, and limb ataxia. We review the ethical issues considered during the process leading to the decision to offer cardiac transplantation.